(3GdeaGgje,GdhXGFa,GdYedjGJs - (3YHO GdcQje(B, (3CHh eUWais ([(3O(B.(3e(B]:s [(3O(B.(3f(B],s, 2001)
(3eaghe GdGOGQI(B-(3GdacQ GdGOGQj(B-(3GdeaGgje GdGOGQjI(B-(3GdJNWjW GdGOGQj(B-(3GdJfXje GdGOGQj(B-(3GJNGP GdbQGQGJ(B-(3GdJehjd(B-(3GdbjGOI hGdJhLjg(B-(3GdJfSjb hGdGJUGdGJ GdEOGQjI(B-(3GdJhLjg hGdQbGHIs
Keywords: (3GdEOGQIs; (3GdJNWjWs; (3GdJfXjes